The Extent of Virtual Reality's Impact on Computer Learning Motivation: A Comprehensive Review of Literature and Educational Research - Albalawi, Amirah Mohammed (Journal of Educational and Psychological Sciences, 2024)
The study aimed to understand how virtual reality (VR) technology impacts computer learning motivation, based on the included studies. The researcher used a systematic review method, evaluating selected studies quantitatively and qualitatively. The research sample included both Arab and foreign studies related to the reality of teachers employing VR in the educational process. The study reviews various teaching methods using VR, identifies best practices, challenges, and the latest technologies in the field. It emphasizes VR's role in enhancing student learning motivation, making learning more meaningful and effective, and discusses how VR can inspire teachers to integrate this technology into their teaching methods. The study recommends using best practices in employing VR, focusing on addressing various challenges such as resistance to new technologies in educational environments, lack of realism and technical challenges, high costs, and difficulties in user interface design and teacher training. The study is important for understanding the use of VR in education, highlighting its benefits, challenges, and impact on learning motivation.
Keywords: Virtual reality; learning motivation; computer instruction